The helminth community of Geophagus proximus (Perciformes: Cichlidae) from a tributary of the Paraná River, Ilha Solteira Reservoir, São Paulo State, Brazil - Zago, A. C. [UNESP]; Franceschini, L. [UNESP]; Zocoller-Seno, M. C. [UNESP]; Veríssimo-Silveira, R. [UNESP]; Maia, A. A D [UNESP]; Ikefuti, C. V. [UNESP]; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2013)
This study aimed to evaluate the helminth parasites of Geophagus proximus from the São José dos Dourados River, a tributary of Paraná River, Ilha Solteira Reservoir, São Paulo State, Brazil. From May 2006 to May 2007, 116 G. proximus specimens were examined and seven different taxa of helminth were collected and identified: proteocephalidean plerocercoids (Cestoda); metacercariae of Austrodiplostomum compactum, Clinostomum heluans and Clinostomum sp. (Trematoda); and Raphidascaris (Sprentascaris) hypostomi, and larvae of Raphidascaris sp. and Contracaecum sp. (Nematoda). All parasites presented the typical aggregated pattern of distribution, as well as the presence of a high number of larval stages, an absence of influence of the host sex and seasonality upon community parameters, as well as a correlation between species richness and host body weight. Moreover, with the exception of A. compactum metacercariae, all helminths found in this study are reported for the first time in G. proximus. Copyright © Cambridge University Press 2012.
Keywords: Austrodiplostomum compactum; body weight; Brazil; cestode; clinostomum; Clinostomum heluans; community structure; Contracaecum; correlation analysis; fauna; female; Geophagus proximus; helminth; larva; male; metacercaria; nonhuman; Perciformes; quantitative analysis; Raphidascaris; Raphidascaris hypostomi; seasonal variation